Prospectus preparation for international private investment; a guide for the developing countries - Robinson, Harry J. (New York : Praeger, 1971)
This book is concerned with the flow of productive private investments across international boundaries. The study had been updated to embrace the many changes that have taken place in the field of international finance, including the creation of new multinational and multiregional development banks and the signing of international agreements and conventions to encourage and safeguard private foreign investments.
Includes bibliographical footnotes.
usc 07/08/18
Loans
Keywords: Investments, Foreign; Prospectus writing; Financial institutions, International